RITUAL KEAGAMAAN MASYARAKAT DAYAK HINDU-BUDHA BUMI SEGANDU INDRAMAYU - I Putu Gede Ardhi Gunawan (STABN Sriwijaya, 2014)
Dayak's tribe is which as we know inltabit ttie island of Borneo, but there arecommunities called themselves Hiruiu-Buddhis! Dayak Bumi Segandu which is located i11Krimun Vilagge, Losarang, lndramayu district. Although if is almost similar to tirepattern of lifeof the Dayak tribe i11 Borneo in ways that are still traditional, but there are interesting things associated with religious rituals iu this comm1111ity that adopts Kejawen because this identity is 1101 affiliated with any religion wlw haue legitimate recognized in tire State of Indonesia. There are two main ritual which is run by tire community, the ritual Kungkum and Pepe. Kw1gkum is a ritual that requires male members of this community to soak at a time or flow from 11ight until morning for four months. Similarly, the ritual Pepe is a ritual with a physical body drying under the s1111. The whole ritual is executed with tire meaning that as a human being should train themseloes to rid yourself of the body, mind, heart and passion of the world and as ,m attempt to overcome the temptations that often occur in man, both physically and me11tally as well as an attempt to blend with the natural which luts berm widely credited for humans.